Pengaruh Ukuran Perusahaan dan Dividen Terhadap Nilai Perusahaan - Andriani, Irma (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2022)
There is an increase and decrease in the value of the company from year to year, many factors affect the value of the company including: company size and dividends. This study aims to prove the effect of firm size and dividends partially and simultaneously in explaining the rise and fall of firm value. This type of research is quantitative research. The research method that the author uses in this research research uses numerical data or numbers. The data analysis technique used in this research is multiple linear analysis. Hypothesis testing is done by using statistical tests, namely t test, F test, and adjusted R square. The results of this study indicate that the results of the t test obtained t arithmetic generated by the variable company size of -3.157 and the dividend variable of -1.446 with a significant level of 0.003 and 0.156, respectively. The results of the significance of 0.003 <0.05, which means that the firm size variable has a negative and significant effect on firm value, and 0.156 > 0.05, which means that it has no partial effect on firm value. The results of the F test obtained that the calculated F is 6.425 with a significance level of 0.004 <0.05, which means that simultaneously, firm size and dividends have an effect on firm value. The adjusted R square test was obtained at 0.201 or 20.1%. This shows the ability to contribute variables of firm size and dividends to firm value by 20.1%. And so that it is influenced by other variables outside the model such as: managerial ownership, institutional ownership, capital structure, profitability, company growth.